2022
DOI: 10.3390/nu15010185
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Complications of Radioligand Therapy with Lutetium-177 and Yttrium-90 in Patients with Neuroendocrine Neoplasms

Abstract: Background: Neuroendocrine neoplasms are a group of tumors deriving from neural crest. They can be located in every tissue, but most commonly in gastrointestinal tract. Targeted therapy with use of radionuclides is an available and acceptable way of treatment, but its long-term safety is still to be determined, especially with sensitive methods. Methods: Study was performed on a group of 42 patients. They underwent full cycle (4 courses; 8–12 weekly intervals) of radioligand therapy with [177Lu]Lu-DOTATATE alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…The decrease of glomerular filtration rate and increase of creatinine serum concentration observed in the present study among patients undergoing radioligand therapy is consistent with the known negative impact of the treatment, but it can also be related to the natural decline in GFR values with age, estimated at approximately 1% in the Central European population [31][32][33]. The authors' prospective study published in 2023 showed a sustained decrease of GFR of about 10% one year after radioligand therapy of NEN patients [34]. Given that the kidneys are the critical organ for radioligand therapy, the greatest concerns and limitations of this treatment arise from the potential injury of the kidneys and permanent reduction in glomerular filtration [35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The decrease of glomerular filtration rate and increase of creatinine serum concentration observed in the present study among patients undergoing radioligand therapy is consistent with the known negative impact of the treatment, but it can also be related to the natural decline in GFR values with age, estimated at approximately 1% in the Central European population [31][32][33]. The authors' prospective study published in 2023 showed a sustained decrease of GFR of about 10% one year after radioligand therapy of NEN patients [34]. Given that the kidneys are the critical organ for radioligand therapy, the greatest concerns and limitations of this treatment arise from the potential injury of the kidneys and permanent reduction in glomerular filtration [35].…”
Section: Discussionsupporting
confidence: 88%
“…Risk factors for bone marrow injury included age > 70 years, impaired kidney function, pre-existing cytopenia, and previous chemotherapy or radiotherapy [37]. The authors' previous study also confirmed that bone marrow function after the RLT was significantly disturbed [34,38]. During RLT a decrease in each bone marrow cell line was observed, however, statistically significant results regarded only leukocytes and lymphocytes.…”
Section: Discussionsupporting
confidence: 55%
“…There is a lack of high-quality double-blind studies comparing monotherapy with [ 177 Lu]Lu-DOTA-TATE with tandem [ 177 Lu]Lu-DOTA-TATE/[ 90 Y]Y-DOTA-TATE, but physical features of 90 Y cause more concerns in using this type of treatment. A possible higher number of adverse events, like decreasing GFR, liver injury, or bone marrow dysfunction, was not statistically proven, with even some data advocating for higher effectiveness of the method in treating large tumors or metastases [13,15,[66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study group were similar to ones observed in previous studies. Despite reaching statistical significancy, the changes in described parameters were not clinically significant [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%